2012
DOI: 10.1021/bi300744z
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazole–Heme Interactions in Cytochrome P450: Functionally Competent Triazole–Water–Heme Complexes

Abstract: In comparison to imidazole (IMZ) and 1,2,4-triazole (1,2,4-TRZ) the isosteric 1,2,3-triazole (1,2,3-TRZ) is unrepresented among CYP inhibitors. This is surprising because 1,2,3-TRZs are easily obtained via ‘click’ chemistry. To understand this underrepresentation of 1,2,3-TRZs among CYP inhibitors, thermodynamic and DFT computational studies were performed with unsusbstituted IMZ, 1,2,4-TRZ, and 1,2,3-TRZ. The results indicate that the lower affinity of 1,2,3-TRZ for the heme iron includes a large unfavorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 56 publications
8
68
2
1
Order By: Relevance
“…thiazole. These results differ in some respects to those described by Conner et al (2012) whose study evaluated the energetics of water exchange by imidazole, 1,2,4-triazole, and 1,2,3 triazole using an identical model system, M06 functional, and the spin-state corrected 6-31G basis set (Swart et al, 2010 ). Notable differences between our results and those described in Conner et al (2012) include the 2-to 5-fold differences in exothermicities as well as the prediction that coordination of imidazole is more exothermic than 1,2,4-triazole.…”
Section: Thiazol-2-ylidene Coordination To Cyp3a4contrasting
confidence: 77%
See 1 more Smart Citation
“…thiazole. These results differ in some respects to those described by Conner et al (2012) whose study evaluated the energetics of water exchange by imidazole, 1,2,4-triazole, and 1,2,3 triazole using an identical model system, M06 functional, and the spin-state corrected 6-31G basis set (Swart et al, 2010 ). Notable differences between our results and those described in Conner et al (2012) include the 2-to 5-fold differences in exothermicities as well as the prediction that coordination of imidazole is more exothermic than 1,2,4-triazole.…”
Section: Thiazol-2-ylidene Coordination To Cyp3a4contrasting
confidence: 77%
“…The K d of thiazole is 3.4 6 1.0 mM at pH 7.4, more than 4800-fold higher than that measured for ritonavir. Additionally, the K d of thiazole is nearly one and two orders of magnitude higher than the K d values measured for 1,2,4-triazole and imidazole (Conner et al, 2012), and, as supported by density functional theory calculations, it is among the weakest azaheterocyclic ligands for thiolateligated Fe 31 -heme. NMTI was synthesized and titrated into the CYP3A4 to lend further support to the concept that the unique features of the Thiazol-2-Ylidene Coordination to CYP3A4 difference spectra were attributed to the deprotonation and coordination of the N-methylthiazolium unit of NMeR.…”
Section: Uv-visible Absorbance Analysis Of Ligand Bindingmentioning
confidence: 60%
“…This is spectroscopically detectable as a shift of the maximum absorbance peak from 417-419 nm to 390-394 nm [31]. On the other hand, type II ligands are nitrogen-containing compounds that displace the water molecule while directly coordinating to the heme iron, or alternatively they form a hydrogen bond with the water molecule present as the sixth ligand [32][33][34]. In the case of type II ligands, the heme iron is hexa-coordinated and the maximum absorbance peak shift from 418 nm to 422-426 nm [35].…”
Section: Uv-vis Spectroscopic Analysis Of Sildenafil Binding To Humanmentioning
confidence: 99%
“…Ketoconazole has been recognized as a weak inhibitor of CYP2C8 as listed in US FDA Guidance for Industry -Drug Interaction Studies (2012) (22), however, there were few reports in terms of the inhibition of CYP2C8 by miconazole (15). It has been established that imidazole and triazole compounds, including azole antifungals, reversibly inhibit drug-metabolizing P450s by heme-nitrogen interactions (23,24). Fluconazole can exhibit competitive, noncompetitive, or mixed-type inhibition against CYP3A4 (14,15,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole competitively inhibited CYP3A4 (15,17,27,29). On the other hand, it has been reported that fluconazole and voriconazole exhibited mixed-type inhibition and competitive inhibition, respectively, against CYP2C9 (14,15,24,30 CYP2C9.1 (14). Thus, the inhibition type seems to be different among substrates, inhibitors (azole antifungals), P450s, and/or other experimental conditions.…”
Section: Discussionmentioning
confidence: 99%